Sculpture, "Pacifica" by Ralph Stackpole
Description attached: Pacifica and Creator: One of the largest statues in the world is this 80-foot figure made by Ralph Stackpole, San Francisco sculptor, for the Court of Pacifica on Treasure Island, San Francisco Bay site of the 1939 Golden Gate International Exposition. Stackpole is standing at the base of the mammoth figure.